TEACHERS' STRATEGIES IN PROMOTING STUDENT QUESTIONING IN EFL CLASSROOMS - Ma'rufah, Desi Wijayanti (2017)
The learning activities in 2013 Curriculum are expected to be interactive, inspiring, fun, and challenging which can motivate students to participate actively in the classroom. Besides, the implementation of Scientific Approach in the 2013 Curriculum is expected to create students as inquiry learners who use critical thinking in discovering certain concepts. Students' participation in discussion, argument, critical thinking, and meaningful learning increase when they ask productive questions in class. However, the Indonesian EFL students still have little space in the classroom interaction, not to mention in student questioning. In particular, teachers have problems in raising students' skills in asking questions and encouraging the participation of students in discussion, arguing, developing the ability to make questions. Accordingly, this study aims to investigate the teachers' strategies in promoting student questioning in the tenth and eleventh grade classes of a senior high school in Purbalingga. A descriptive qualitative study was conducted through observation, interview and questionnaire to reveal the findings of the study. The results show that the teachers used various strategies in promoting student questioning. The present study concludes that Indonesian EFL students would be promoted to ask productive questions in class when the teachers: (a) considered and set activity which required the students to construct and pose questions in class; (b) provided objects or topic of questioning which were able to scaffold the students in asking questions; (c) provided an accepting questioning classroom climate to make the students to ask questions actively, safe and confidently; (d) explicated the instructions covering the range of questioning activity and topic of questions that the students should do. The study implies that student questioning is important to be considered since it can be as one of the efforts in achieving the 2013 Curriculum aims. It is also suggested teachers practice the strategies in promoting student questioning continuously so that the students' problem of participation is able to be resolved. Keywords: student questioning, teacher strategies, interactive classroom, critical thinking Dalam Kurikulum 2913, aktifitas dalam pembelajaran diharapkan disajikan secara interaktif, menginspirasi, menyenangkan dan menantang yang dapat memotivasi siswa untuk berpartisipasi secara aktif di dalam kelas. Selain itu, implementasi Scientific Approach dalam Kurikulum 2013 ditujukan untuk membentuk siswa sebagai inquiry learners yang menggunakan pikiran kritis dalam menemukan suatu konsep. Partisipasi siswa dalam berdiskusi, berargumen, berpikir kritis dan pembelajaran yang bermakna dapat meningkat ketika siswa bertanya secara produktif di kelas. Namun, siswa EFL di Indonesia masih memiliki kesempatan yang sedikit dalam interaksi kelas termasuk siswa bertanya di kelas. Khususnya, guru memiliki masalah dalam meningkatkan kemampuan siswa bertanya dan mendorong partisipasi siswa dalam berdiskusi, berargumen, dan mengembangkan kemampuan untuk bertanya. Berdasarkan hal tersebut, thesis ini bertujuan untuk menginvestigasi strategi guru dalam mendorong siswa bertanya di kelas sepuluh dan sebelas di salah satu SMA di Purbalingga. Penelitian deskripsi kualitatif dilakukan melalui observasi, interviu, dan angket untuk menemukan hasil dari penelitian ini. Penelitian ini menyimpulkan bahwa siswa EFL di Indonesia akan terdorong untuk bertanya secara produktif di kelas ketika guru (a) memperhatikan dan mempersiapkan aktifitas yang menuntut siswa untuk membuat dan bertanya di kelas; (b) menyediakan objek dan topik untuk bertanya; (c) menyediakan suasana kelas yang menerima pertanyaan siswa di kelas; (d) memberikan instruksi yang jelas kepada siswa untuk bertanya. Penelitian ini mengimplikasikan bahwa pertanyaan siswa penting untuk diperhatikan karena hal ini dapat sebagai salah satu usaha untuk mencapai tujuan Kurikulum 2013. Disarankan kepada guru untuk mempraktekan strategi dalam mendorong siswa untuk bertanya secara berkelanjutan sehingga masalah partisipasi siswa dapat terpecahkan. Kata kunci: student questioning, teacher strategies, interactive classroom, critical thinking